ANALISIS POTENSI FAKTOR PENYEBAB BANJIR DI KECAMATAN DAYEUHKOLOT KABUPATEN BANDUNG - heryanti, adila sani; noveriza supryatna, keyra syifa; rahayu , yayu; septiadi, muhammad andi (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2025)
Recurrent flooding in Dayeuhkolot District, Bandung Regency, demonstrates the ineffectiveness of disaster risk reduction policy implementation. This study aims to evaluate the implementation of these policies in building regional resilience to flooding. The method used is descriptive qualitative with triangulation techniques through interviews, observations, and documentation studies. The results show that flooding is triggered by natural factors (high rainfall, basin topography), technical (inadequate drainage), and social (population density, waste disposal behavior, and low community participation) factors. The conclusion of this study shows that these three natural, technical, and social factors are interrelated and collectively increase the region's vulnerability to flooding, while the implementation of flood risk reduction policies is considered suboptimal due to weak coordination between institutions and minimal active community involvement. This study contributes to providing a basis for the formulation of more adaptive, collaborative, and locally appropriate policies to strengthen regional resilience to flooding.